Penafsiran Kontekstual Kesaksian Perempuan - Arifin, Muhammad Patri (Pusat Studi Gender dan Anak, IAIN Palu, 2017)
The position of women in Islam still holds a problem that is an imbalance or bias between the position of men and women. One of the causes of the emergence of such imbalances is the religious teachings that place the woman in a disadvantaged position compared to the men’s position. Religious teachings can be represented by the content of the Qur'an and Hadith, while the understanding of religious teachings can be found from the sheets of books tafsir fikih and syarah hadith of the Prophet. Among the Qur'anic verses that some have considered to be discriminatory and gender biased are surah Al Baqarah verse 282 on the testimony of women in debt transaction. To contextualize this verse, the understanding of the historical situation, whether the macro situation (State of the Arabian peninsula) as well as micro situations (asbab an nuzul) which is a very appropriate step to eliminate such discriminatory stigma. At that time, the context of women did not have sufficient experience in financial m tters which at that time was dominated by men. So the problem is not on the gender whether male or female, but on credibility when it was given to be a witness.